Race in another America: the significance of skin color in Brazil - Telles, Edward E. (Princeton University Press, 2004)
Introduction -- From white supremacy to racial democracy -- From racial democracy to affirmative action -- Racial classification -- Racial inequality and development -- Racial discrimination -- Intermarriage -- Residential segregation -- Rethinking Brazilian race relations -- Designing appropriate policies